Assessing capacities of older adults : a casebook to guide difficult decisions - Moye, Jennifer (American Psychological Association, 2020)
"This book demonstrates how to address practical and ethical challenges when evaluating capacities of older adults with neurocognitive disorders, like dementia. The contributors are expert clinicians who draw upon real life experiences conducting clinical capacity assessments in civil matters, illustrating best practices based on the guidelines from the ABA/APA's Assessment of Older Adults with Diminished Capacity: A Handbook for Psychologists. Chapters cover complex and difficult issues in careful detail, including: * financial exploitation, * undue influence, * sexual consent, and * medical aid in dying. The author also provides guidance for negotiating family conflicts, working with surrogate decision makers who also have diminished capacity, coordinating with medical and legal professionals, and addressing other situations that involve multiple stakeholders with competing priorities. A recurring theme throughout the volume is the challenge of balancing a client's right to autonomy, while also protecting them from harm. The book offers careful, effective advice for keeping clients who lack decision making capacity involved in their healthcare choices and working to maintain their independence when daily living skills are impaired"--